Juror Delinquency in Criminal Trials in America, 1796-1996 - King, Nancy J. (1996)
This article examines two aspects of the jury system that have attracted far less attention from scholars than from the popular press: avoidance of jury duty by some citizens, and misconduct while serving by others. Contemporary reports of juror shortages and jury dodging portray a system in crisis.' Coverage of recent high-profile cases suggests that misconduct by jurors who do serve is common. In the trial of Damian Williams and Henry Watson for the beating of Reginald Denny, a juror was kicked off for failing to deliberate; Exxon, Charles Keating, and the man accused of murdering Michael Jordan's father all complained of juror misconduct; and, of course, several jurors in the trial of O.J. Simpson were replaced after allegations that they had lied, concealed intentions to profit from the case, or otherwise misbehaved. In the past year, newspaper reports have described less well-known cases in which jurors refused to answer personal questions, stole jewels introduced as evidence, had sex with courthouse deputies, visited the crime scene, bit another juror's arm to examine tooth marks, read forbidden newspaper articles, got drunk, made racist comments, used drugs, and discussed the case before the end of the trial. The research reported here is an effort to place these defects in the jury system into perspective, to learn how widespread these problems are, whether they are new (or, if not, how they differ from similar problems in earlier years), and what courts have done and should do now about them. The article incorporates a historical overview of jury dodging and misconduct since 1796 and the results of an original survey completed in December, 1995, by 562 trial judges across the country. The survey is the first to collect empirical information about jury avoidance and misconduct nationwide